1994
DOI: 10.1073/pnas.91.9.3857
|View full text |Cite
|
Sign up to set email alerts
|

Protection from endotoxic shock in mice by pharmacologic inhibition of phosphatidic acid.

Abstract: Certain phosphatidic/plasmanic/plasmenic acid (PA) species function as lipid intermediates in cell activation and may function directly as intracellular signaling molecules. PA can also be dephosphorylated to 1,2-diradyl-snglycerol by phosphatidate phosphohydrolase. Treatment of various cell types, including murine P388 monocytic leukemia cells, with bacterial lipopolysaccharide rapidly stimulates large increases in PA and PA-derived diradylglycerol. Pentoxifylline, 1-(5-oxohexyl)-3,7-dimethylxanthine, inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 28 publications
1
65
2
Order By: Relevance
“…In contrast, the product of LPA acylation is PA. A number of recent reports have suggested that PA may be a key intracellular messenger in a common signaling pathway activated by proinflammatory mediators such as IL-1␤, tumor necrosis factor-␣, platelet-activating factor, and lipid A (29,32,33). That this PA is generated by the action of LPAAT was demonstrated by the observation that small molecule inhibitors of the enzyme block PA formation in P388 monocytic leukemia cells stimulated with bacterial lipopolysaccharide (35) and in hypoxia-treated human neutrophils (36). The small molecule inhibitors also protected mice from lipopolysaccharide-mediated endotoxic shock and from lung injury in a model of hemorrhage and resuscitation (36).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the product of LPA acylation is PA. A number of recent reports have suggested that PA may be a key intracellular messenger in a common signaling pathway activated by proinflammatory mediators such as IL-1␤, tumor necrosis factor-␣, platelet-activating factor, and lipid A (29,32,33). That this PA is generated by the action of LPAAT was demonstrated by the observation that small molecule inhibitors of the enzyme block PA formation in P388 monocytic leukemia cells stimulated with bacterial lipopolysaccharide (35) and in hypoxia-treated human neutrophils (36). The small molecule inhibitors also protected mice from lipopolysaccharide-mediated endotoxic shock and from lung injury in a model of hemorrhage and resuscitation (36).…”
Section: Discussionmentioning
confidence: 99%
“…Also, clonidine's anti-allodynic effects were mimicked by apraclondine, which does not cross the blood brain barrier 83 . In addition, the many of the various anti-inflammatory activities of pentoxifylline and lisofylline are linked with their vascular effects 7,62,76,91 , as microvascular function is key to various processes involved in the inflammatory response, including plasma extravasation, platelet aggregration, leukocyte migration, cytokine activation, among others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clonidine acts at imidazoline receptors as well as α 2A receptors 88 , and pentoxiphylline is a non-specific PDE inhibitor that produces anti-inflammatory effects by interacting with various biological systems. Furthermore, although lisofylline is a phosphatidic acid inhibitor, it is a metabolite of pentoxifylline 62,76 , and shares many of pentoxifylline's PDE inhibitor activities, including inhibition of various cytokines 76 . However, topical administered clonidine is unlikely to have significant effects at brainstem imidazoline receptors, especially at the low concentrations we have used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations